« Ethnographies » au service du développement de compétences scientifiques dans l’éducation préscolaire et l’enseignement de premier cycle dans la région des Açores - Ludivine Egounleti (Éducation et Socialisation)
The aim of this article is to question the methodology used by the first grade and preschool’s teachers, training for the master degree in First grade and pre-school teaching in the University of Azores. It is to assess the development of children’s scientific competences in primary school and pre-school. The « ethnographic register » so called by the students and teachers involved in the research will be analyzed as a scientific tool that enables the reading of development index of scientific competences. The use of double quotes refers to diverse uses of the term « ethnography ». Though, it will be put into perspective their use of the term « ethnographic register » and the actual ethnographic methodology used to analyze children’s behavior.